Improving groundwater management for Indian agriculture: Assessing tradeoffs across policy instruments - Msangi, Siwa; Cline, Sarah Ann (World Scientific Publishing, 2016)
Despite efforts to reform management of water resources, groundwater levels have continued to decline steadily in key aquifers across India, leading to serious environmental concerns and impacts. While policy makers have looked to efforts aimed at improving the efficiency of field-level irrigation and strengthening ownership and property rights in local resource management, hydrologists have asserted that more direct control of consumptive use patterns of water is needed. In this paper, we illustrate the divergence between current groundwater usage patterns and an optimal path, in which the groundwater levels are stabilized with better demand-side management. The paper assesses the tradeoffs embedded in alternative policy instruments that are aimed at modifying the groundwater pumping behavior of agricultural water users. The challenges of regulating smallholder agricultural water users are shown to be relevant in determining which instrument might have the best chance of slowing the depletion of groundwater resources in the hard-rock aquifers of India, and promoting the long-run sustainability of this critical natural resource.